Tren pemberitaan sonokeling dalam portal berita daring di Indonesia - Indira Riastiwi; I Putu Gede P. Damayanto (Berkala Ilmu Perpustakaan dan Informasi, 2022)
Introduction. It has never been a study on the news trend of rosewood in Indonesia. This study aimed to determine the trend of rosewood news in online news portals and to create a distribution map of rosewood planting locations in Indonesia. Data Collection Method. Data were obtained by collecting online news related to rosewood from 2016‒2022. Data were compiled and analyzed descriptively. A distribution map of rosewood was made and superimposed with data from Global Biodiversity Information Facility. Results and Discussions. The number of rosewood news in Indonesia on online news portals increased from 2016‒2022. The most topic of the news is criminal (illegal logging and distribution of woods), followed by the topic of economic (woods potential use), disasters (trees fallen), social (tree-planting movements), and political (wood distribution regulation), respectively. In Indonesia, rosewood was planted in Jambi, Lampung, West Java, Central Java, DI Yogyakarta, East Java, Bali, West Nusa Tenggara, and East Nusa Tenggara, which correspond to the areas of rosewood cultivation and distribution in Indonesia. Conclusions. The number of rosewood news in Indonesia on online news portals increased from 2016‒2022, dominated by criminal topics. In Indonesia, rosewood was planted in southern Sumatra, Java, Bali, and Nusa Tenggara.